New perspectives on ritual in the Biblical world - Quick, Laura 1987-; Ramos, Melissa D. (London [England] T&T Clark, 2022)
"This volume presents a range of methodologically innovative treatments on ritual action in the Hebrew Bible. They treat a diverse range of ritual phenomena, including space, blessings and oath-taking, from the world of ancient Israel and Judah. The introduction engages with the dominant scholarly models drawn from ritual theory, and the volume explores their applicability to ancient textual material such as the Hebrew Bible. The chapters reflect high-level specialized engagement with specific ritual phenomena through the lens of appropriate theoretical and methodological approaches."--
List of Abbreviations Introduction Part 1: Bodies, Gender and Ritual -- 1. An Indecent Proposal or a Ritualized Quest for Survival? The Threshing Floor Episode in Ruth 3 Reconsidered, Ekaterina E. Kozlova, London School of Theology, UK -- 2. Ritual, Gender, and History in 1-2 Kings, Cat Quine, University of Nottingham UK 3. Milk, Meat, and Mothers: The Problem of Motherhood in Some Ritual Food Laws, Nicole Ruane, University of New Hampshire, UK -- 4. Drinking the Golden Calf: Consumption and Transformation in Exodus 32, Laura Quick, University of Oxford, UK Part II: Magic and Ritual 5. Satan and the High Priest: Zechariah 3 as Exorcism, Isabel Cranz, University of Pennsylvania, USA -- 6. Contested Divination: Biblical Necromancy and Competition among Ritual Specialists in Ancient Israel, Kerry Sonia, Colby College, USA -- 7. Binding Asmodeus: A Lexical Analysis of the Ritual and Medical Use of Fish in Tobit , Lindsay Askin, University of Bristol, UK -- 8. Enchant the Sabbath Day to Make it Holy: Conjuration and Performativity in Exodus 20:8-11, Timothy Hogue, UCLA and Loyola Marymount University, USA Part III: Textualization and Ritual 9. Aaron' Body as Ritual Vessel, Alice Mandell, Johns Hopkins University, USA 10.The Literary Representation of Sacrifice in Biblical Narrative, Liane Feldman, New York University, USA 11. "The Offerings of the Tribal Leaders, the Purification of the Levites, and the Hermeneutics of Ritual Innovation", Nathan MacDonald, Cambridge University, UK -- 12. Monumentalizing Slaughter: ́€ÿCutting a Covenant́€Ö in the Hebrew Bible and Levantine Inscriptions, Melissa Ramos, George Fox University, USA -- 13. Silver Scripts: The Ritual Function of Purified Metal in Ancient Judah, Jeremy Smoak, UCLA, USA -- Bibliography -- Index
Includes bibliographical references and index
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: BIble -- Criticism, interpretation, etc; Ritual